Ultrastructure of the spermatophores and spermatozoa from the gecarcinid land crab, Cardisoma guanhumi Latreille, 1828, (Crustacea, Brachyura, Gecarcinidae) from the western Atlantic - Benetti, Aline Staskowian; Tavares, Marcos; Dos Santos, Daniela Carvalho [UNESP]; Tudge, Christopher (Taylor & Francis, 2013)
The ultrastructure of the sperm of the gecarcinid land crab Cardisoma guanhumi is described by scanning and transmission electron microscopy. Ultrastructural sperm morphology lends support for the monophyletic origin of the Thoracotremata, and for the placement of C. guanhumi in that clade. Additionally, it further attests the low level of variability within the thoracotreme clade. With regard to ultrastructural morphology, small differences concerning the apical button, the hyaline periopercular rim, the inner acrosome zone, and the outer two lamellations in the outer acrosome zone have been found between the spermatozoa of C. guanhumi and Cardisoma carnifex, the only other species in this genus studied for spermatozoal morphology. Copyright © 2013 Taylor & Francis.
Keywords: SEM; Sperm morphology; Spermatophore; TEM; Thoracotremata